Evaluation on Hazards and Risks Related to Scaffolding Activity at Construction Site - Salihin, Syahmi; Ezrin Hani Sukadarin,; Muhamad Amin Abd Hamid, (Progress in Engineering Application and Technology, 2024)
Abstract: This study aims to evaluate the effectiveness of scaffold safety practices in the construction industry, with a focus on identifying common safety issues and potential areas for improvement. The research will utilize a comprehensive checklist to assess supported scaffold safety practices at construction sites, considering technical, human, and organizational factors. Additionally, the study will examine the impact of the revised scaffold safety standards on accident prevention and overall safety performance in the industry. The findings are expected to contribute to the development of enhanced safety management systems and the identification of key areas for further research and intervention to mitigate scaffold-related accidents at construction sites.This abstract is based on the evaluation of scaffold safety practices in construction, the effectiveness of the revised scaffold safety standard in the construction industry, and the factors influencing scaffold-related accidents at construction sites Keywords: